ANALISIS PENERAPAN PSAK 48 (REVISI 2014 PADA PT GUDANG GARAM TBK - Wijayanti, Fitria; Solikah, Mar’atus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2017)
Each company has factors that can support the production process, one of which is a fixed asset. Each fixed asset will experience impairment due to usage, since the recoverable amount is less than the asset's carrying amount. The building is one of the disadvantaged fixed assets over time. The purpose of this study is to determine the application of impairment of fixed assets at PT. Gudang Garam Tbk. The year 2012-2016 has been in accordance with PSAK 48. This type of research is descriptive quantitative. The object of this study is the financial statements. PT. Gudang Garam Tbk period of December 31, 2012, 2013, 2014, 2015, and 2016. Data collection techniques using field studies, namely dengn amengabil financial statements that have been published on the Indonesia Stock Exchange. The analysis used is quantitative descriptive by comparing the application of impairment of assets used in the company and PSAK 48. Based on the results of the analysis conducted, it can be seen that there is no impairment in the fixed assets of buildings in PT. Gudang Garan Tbk and the methods used in its calculations are in accordance with PSAK 48.